2007
DOI: 10.1017/s0007114507742708
|View full text |Cite
|
Sign up to set email alerts
|

Association between insulin-like growth factor-1, insulin-like growth factor-binding protein-1 and leptin levels with nutritional status in 1–3-year-old children, residing in the central region of Limpopo Province, South Africa

Abstract: The present study evaluated levels of growth factors and their associations with nutritional status with emphasis on stunting in children at 1 and 3 years of age. A follow-up study on a birth cohort (n 219) of children from villages in the central region of the Limpopo Province was undertaken. Of the original cohort, 156 and 162 could be traced and assessed at ages 1 and 3 years, respectively. Data collected included socio-demographic characteristics, anthropometric measurements, dietary intake and fasting blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…The higher prevalence of stunting among infants and young children (0–2-year-old) from low socio-economic areas ( 22 , 27 , 30 ) compared to higher socio-economic urban areas ( 19 , 28 , 31 , 38 ) is in line with the previous review ( 8 ) and a recent review of global data ( 86 ) . The highest total under 5 years old prevalence of stunting, underweight and wasting was found among children from the Northern Cape province, where a large proportion of the population live in under-resourced settings ( 33 35 ) .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The higher prevalence of stunting among infants and young children (0–2-year-old) from low socio-economic areas ( 22 , 27 , 30 ) compared to higher socio-economic urban areas ( 19 , 28 , 31 , 38 ) is in line with the previous review ( 8 ) and a recent review of global data ( 86 ) . The highest total under 5 years old prevalence of stunting, underweight and wasting was found among children from the Northern Cape province, where a large proportion of the population live in under-resourced settings ( 33 35 ) .…”
Section: Discussionsupporting
confidence: 89%
“…Meta-analysis of all prevalence data shows a stunting prevalence of 25·0 % among infants and preschool children. Generally, a higher prevalence of stunting was reported in rural settings (18–37 %) ( 21 27 ) than in urban areas (1·8–10·9 %) ( 19 , 28 , 29 ) , except for two studies that reported high prevalence of stunting in low socio-economic settings in urban areas (19–36 %) ( 30 32 ) . In regional, as well as in national studies, for the total under 5 years old group, the highest prevalence of stunting, underweight and wasting was found in children from the Northern Cape province ( 33 35 ) .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…IGF-1 was decreased from birth to 24 months old but increased after the age of 24 months [ 56 ]. Another study showed there was no difference of IGF-1 levels based on nutritional states (normal; stunted; overweight; stunted and overweight) [ 57 ], which supports this study.…”
Section: Discussionsupporting
confidence: 86%